Pengaruh Kegiatan Keagamaan terhadap Kualitas Pendidikan - Syukri, Icep Irham Fauzan; Rizal, Soni Samsu; Al Hamdani, M. Djaswidi (Jurnal Penelitian Pendidikan Islam, 2019)
This study aims to determine the effect of religious activities on the quality of education in Madrasah Tsanawiyah Negeri 4 Pangandaran. This study uses correlational quantitative descriptive methods. Data collection using observation techniques, questionnaires, and documentation. The steps of analyzing research data include: data editing, scoring, prerequisite tests, and hypothesis testing. The results showed that: First, Religious Activities in Madrasah Tsanawiyah Negeri 4 Pangandaran included in the sufficient category. Second, the Quality of Education in Madrasah Tsanawiyah Negeri 4 Pangandaran is included in the sufficient category. Third, there is a significant influence between religious activities on the quality of education in Madrasah Tsanawiyah Negeri 4 Pangandaran. This is consistent with the results of SPSS 20 analysis that the sig value of 0,000 <0.05 shows that there is an influence of religious activities on the quality of education.